The Palgrave Handbook of Family Policy - Nieuwenhuis, Rense; Van Lancker, Wim (Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
"This engaging collection gathers theoretical and empirical insights from leading family policy experts. The authors - representing diverse countries, disciplines, and methods - bring to life the volume's innovative conceptual framework, which is organized around policy institutions, both public and private. The volume closes with a call for new lines of research that should inform family policy scholars for years to come." - Janet Gornick, Professor of Political Science and Sociology, and Director of the Stone Center on Socio-Economic Inequality, The Graduate Center, City University of New York, USA "Featuring exciting contributors from a range of often-siloed scholarly disciplines, countries and cultures, this Handbook offers nuanced insights into how interacting societal inequality factors influence family policy enactment to reinforce or improve inequality outcomes across gender, class, and nations. It is ambitious, broad-reaching, and succeeds in providing a strategic view within and across nations to inspire thoughtful evidence-based policy implications to improve societies in the future." - Ellen Ernst Kossek, Basil S. Turner Professor of Management, Purdue University, USA This open access handbook provides a multilevel view on family policies, combining insights on family policy outcomes at different levels of policymaking: supra-national organizations, national states, sub-national or regional levels, and finally smaller organizations and employers. At each of these levels, a multidisciplinary group of expert scholars assess policies and their implementation, such as child income support, childcare services, parental leave, and leave to provide care to frail and elderly family members. The chapters evaluate their impact in improving children's development and equal opportunities, promoting gender equality, regulating fertility, productivity and economic inequality, and take an intersectional perspective related to gender, class, and family diversity. The editors conclude by presenting a new research agenda based on five major challenges pertaining to the levels of policy implementation (in particular globalization and decentralization), austerity and marketization, inequality, changing family relations, and welfare states adapting to women's empowered roles.